A Delphi survey to determine how educational interventions for evidence-based practice should be reported: Stage 2 of the development of a reporting guideline - Phillips, Anna C; Lewis, Lucy K; McEvoy, Maureen P; Galipeau, James; Glasziou, Paul; Hammick, Marilyn; Moher, David; Tilson, Julie K; Williams, Marie T (Université d'Ottawa | University of Ottawa, 2014)
Abstract Background Undertaking a Delphi exercise is recommended during the second stage in the development process for a reporting guideline. To continue the development for the Guideline for Reporting Evidence-based practice Educational interventions and Teaching (GREET) a Delphi survey was undertaken to determine the consensus opinion of researchers, journal editors and educators in evidence-based practice (EBP) regarding the information items that should be reported when describing an educational intervention for EBP. Methods A four round online Delphi survey was conducted from October 2012 to March 2013. The Delphi panel comprised international researchers, educators and journal editors in EBP. Commencing with an open-ended question, participants were invited to volunteer information considered important when reporting educational interventions for EBP. Over three subsequent rounds participants were invited to rate the importance of each of the Delphi items using an 11 point Likert rating scale (low 0 to 4, moderate 5 to 6, high 7 to 8 and very high >8). Consensus agreement was set a priori as at least 80 per cent participant agreement. Consensus agreement was initially calculated within the four categories of importance (low to very high), prior to these four categories being merged into two (<7 and ≥7). Descriptive statistics for each item were computed including the mean Likert scores, standard deviation (SD), range and median participant scores. Mean absolute deviation from the median (MAD-M) was also calculated as a measure of participant disagreement. Results Thirty-six experts agreed to participate and 27 (79%) participants completed all four rounds. A total of 76 information items were generated across the four survey rounds. Thirty-nine items (51%) were specific to describing the intervention (as opposed to other elements of study design) and consensus agreement was achieved for two of these items (5%). When the four rating categories were merged into two (<7 and ≥7), 18 intervention items achieved consensus agreement. Conclusion This Delphi survey has identified 39 items for describing an educational intervention for EBP. These Delphi intervention items will provide the groundwork for the subsequent consensus discussion to determine the final inclusion of items in the GREET, the first reporting guideline for educational interventions in EBP.